Motion Events in L1 and L2 Mapudungun Narratives: Typology and Cross-Linguistic Influence - Becerra, Rodrigo; Osorio, Jorge; Cantarutti, Ítalo; Llanquinao, Gabriel (Frontiers in Communication, 2022)
We compare the motion lexicalization patterns produced by L1 and L2 speakers of Mapudungun, an indigenous minority language spoken in Chile and Argentina. According to previous descriptions, the patterns of motion expression in Mapudungun have some characteristics of an equipollently-framed language, which contrast with the usual motion expression in Spanish. The data comprise oral narratives of the picture storybook “Frog, where are you?”, collected from 10 Mapudungun native speakers and 9 Spanish native speakers who are late bilinguals of Mapudungun. We report the general results (comparison of total clauses, translational clauses, types, and tokens) and analyze three general conflation patterns: the encoding of the semantic components of Path and Manner, the conflation of various components into serial verb constructions, and the encoding of Ground. The results show that L2 speakers encoded a significantly lower proportion of Manner verbs and a higher proportion of Path verbs than L1 speakers, used a significantly less diverse inventory of Path and Manner verb types, a significantly lower number of motion serial verb constructions, and a significantly higher number of plus-Ground clauses than L1 speakers, suggesting cross-linguistic influence from Spanish.